The Ebbs and Flows of Attachment: Within-Person Variation in Attachment Undermine Secure Individuals’ Relationship Wellbeing across Time - Girme, Yuthika U. (J Pers Soc Psychol, 2017)
Although attachment security is relatively stable over time, individuals do experience significant within-person variation in their attachment security across time. No research to date, however, has assessed the relational consequences of within-person variation (fluctuations) in attachment security toward a specific attachment figure. Study 1 (N = 409) first examined whether attachment security was associated with individuals’ expectations that their current intimate relationship would be stable and consistent over time (versus inconsistent and unstable). Studies 2 and 3 extended this by examining the prevalence and consequences of actual within-person variation (fluctuations) in relationship-specific attachment security toward an intimate partner in two multi-wave longitudinal studies that assessed individuals (Study 2, N = 324) and couples (Study 3, N = 171 dyads). The results indicate that secure individuals (those low in attachment anxiety or attachment avoidance) expect their current relationship to remain relatively stable and consistent over time (Study 1). However, Studies 2 and 3 demonstrated that most individuals do experience fluctuations in their relationship-specific attachment security. Moreover, greater fluctuations predict declines in relationship satisfaction (Studies 2 and 3) and increases in relationship distress (Study 3) over time, but primarily for secure individuals (those low in baseline attachment anxiety or attachment avoidance). This set of findings highlight the importance of examining within-person fluctuations in attachment security, which are associated with declines in trajectories of relationship wellbeing, particularly for secure individuals who anticipate greater stability in their relationships.